2021
DOI: 10.3390/agriculture11111071
|View full text |Cite
|
Sign up to set email alerts
|

Profile of the Small-Scale Farms Willing to Cooperate—Evidence from Lithuania

Abstract: Cooperatives cover a large part of the agricultural sectors and have substantial market shares in agri-food supply chains in the EU Western countries. They account for approximately half of agricultural trade in the EU. By contrast, in the EU Western countries, where farmer cooperatives are widespread and successful, agricultural cooperation in Lithuania has developed intermittently in the last century. We still have very limited knowledge of why the country’s agricultural producers (especially smallholder far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…While only 9.1% of the members supply input from cooperatives and unions, the joining ratio of the members at training programs and general meeting were 29.7% and 17.6%, respectively. Drozdz et al (2021) found that the average age of farmers who were willing to cooperate were 46 years and 45%, 40%, 10% and 5% of the farmers graduated from higher bachelor degree, vocational, higher master degree and general, respectively in Lithuania. Abdelhafidh et al (2022) emphasized that because education and training improve farmers' human capacities which lead to the efficiency's increase have important positive marginal effects on the WTP.…”
Section: Socio-economic Characteristics Of Membersmentioning
confidence: 99%
See 2 more Smart Citations
“…While only 9.1% of the members supply input from cooperatives and unions, the joining ratio of the members at training programs and general meeting were 29.7% and 17.6%, respectively. Drozdz et al (2021) found that the average age of farmers who were willing to cooperate were 46 years and 45%, 40%, 10% and 5% of the farmers graduated from higher bachelor degree, vocational, higher master degree and general, respectively in Lithuania. Abdelhafidh et al (2022) emphasized that because education and training improve farmers' human capacities which lead to the efficiency's increase have important positive marginal effects on the WTP.…”
Section: Socio-economic Characteristics Of Membersmentioning
confidence: 99%
“…Literature review shows that there is a lot of study about willingness to pay for agricultural cooperatives. Many of these researches is about willingness of farmers to cooperate (Kovacic et al, 2000;Baranyai et al, 2008;Antonova et al, 2021;Drozdz et al, 2021). Research has begun to be investigate about members' willingness to pay capital for agricultural organizations in recent times (Newbery et al, 2013;Alho, 2016;Alho, 2019;Kilic Topuz, 2020;Fischer et al, 2021;Nzowa et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, countries all over the world generally pay attention to the development of cooperatives. For example, cooperatives account for about half of the European agricultural trade [ 7 , 8 ]. As for China, almost the Central No.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers assess the level of willingness to cooperate among small farmers in Lithuania and elaborate the profiles of small farms that participate and intend to join cooperatives and, conversely, that do not participate in cooperatives and do not intend to do so [5]. The results show that only 8% of the surveyed farms participate in producer groups or cooperatives, while another 8% intend to participate.…”
mentioning
confidence: 99%